Safety and efficacy of microscope-assisted thyroidectomy (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Due to closely related structures like recurrent laryngeal nerve and parathyroid gland, thyroid surgery becomes challenging. Microscope assisted surgery has better visualization for dissection, and decreases the risk of injury to the nerve, parathyroid gland, and its vascular pedicle. Hence it decreases the operative complications.Method: This is a retrospective study of microscope-assisted thyroidectomy at Gandaki Medical College Teaching Hospital, Nepal from January 2017 to December 2019. Ethical approval was obtained from Institutional review committee. Types of surgery, postoperative hypocalcemia and recurrent laryngeal nerve function were analyzed descriptively.Result:  Out of total 48 microscope assisted thyroidectomy, 41 were female, 42(87.5%) benign pathology, 6(12.5.%) malignant. Hemithyroidectomy was done in 40(83.4%), total thyroidectomy 4 (8.2%), total thyroidectomy with neck dissection  3(6.3%), and completion thyroidectomy with neck dissection in 1(2.1%). Among total thyroidectomies, transient hypocalcemia occurred in 2(4.2%) and temporary recurrent laryngeal nerve palsy in 1(2.1%). No complication occurred in hemithyroidectomies.Conclusion: Microscope-assisted thyroidectomy is a safe procedure which leads to reduced complication of hypocalcemia and recurrent never palsy.